Research for Practice: Vigorous Public Debates in Academic Computer Science. - REGEHR, JOHN (Communications of the ACM, 2017)
The article discusses various issues related to academic computer science research. Topics include debates on software-development methodology in relation to independent faults, a debate on the evaluation of file system performance, and the use of software-based attestation (SWATT) as a protocol for checking memory images from remote systems.